1989
DOI: 10.1002/bmc.1130030210
|View full text |Cite
|
Sign up to set email alerts
|

Rapid purification of detergent‐solubilized bovine hormone‐sensitive lipase by high performance hydrophobic interaction chromatography

Abstract: Hormone-sensitive lipase (HSL), the enzyme controlling the rate of adipose tissue lipolysis and also possibly involved in the regulation of steroidogenesis, has been purified from bovine omental adipose tissue. Partially detergent-solubilized, delipidated and purified HSL was obtained through step-elution at conventional DEAE ion-exchange chromatography, followed by concentration on hydroxylapatite. High performance hydrophobic interaction chromatography (HPHIC) on phenylsilica then resulted in an increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…This activity was given the name hormone-sensitive lipase in 1964 by Vaughan et al (173), who also made the distinction between HSL and MGL, based on differences in pH optimum and substrate specificity. HSL purified from adipose tissue is a hydrophobic and labile protein with an apparent M r of 84,000 (6, 42,[112][113][114]. Following the cDNA cloning of HSL (73), powerful expression systems were established based on baculovirus/insect cell technology, providing large amounts of homogenous protein for structural and functional studies (21, 120c).…”
Section: Identification Of Hsl In Adipose Tissuementioning
confidence: 99%
“…This activity was given the name hormone-sensitive lipase in 1964 by Vaughan et al (173), who also made the distinction between HSL and MGL, based on differences in pH optimum and substrate specificity. HSL purified from adipose tissue is a hydrophobic and labile protein with an apparent M r of 84,000 (6, 42,[112][113][114]. Following the cDNA cloning of HSL (73), powerful expression systems were established based on baculovirus/insect cell technology, providing large amounts of homogenous protein for structural and functional studies (21, 120c).…”
Section: Identification Of Hsl In Adipose Tissuementioning
confidence: 99%
“…After adding salt (0.8 M NaCl final concn.) the eluted protein was subjected to hydrophobic-interaction chromatography on phenyl-Sepharose CL-4B (Pharmacia), essentially as described for the purification of bovine adipose-tissue HSL on phenylsilica [11] : The pooled material was applied to a phenyl-Sepharose column (100 ml) that had been equilibrated with 20 vol. of 5 mM potassium phosphate (pH 7.4)\2 M NaCl\2 % C "$ E "# \1 mM dithioerythritol\10 % glycerol, followed by 10 vol.…”
Section: Infection Of Sf9 Suspension Cultures Hsl Overexpression Andmentioning
confidence: 99%
“…Since the recombinant enzyme is intended for studies requiring a high degree of purity of the protein, such as crystallization studies, a purification scheme resulting in large amounts of homogenous enzyme was established. A modification of previous purification schemes for rat and bovine adipose-tissue HSL, utilizing HPLC and Mono Q [10] and phenyl-silica [11], was employed. The result of such a purification scheme starting with 12 litres of culture (approx.…”
Section: Large-scale Production and Purification Of Hsl In Insect Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial step of lipolysis is the hydrolysis of triacylglycerols (Montague and O'Rahilly, 2000). In adipose tissue of cows, it is suggested that hydrolysis of triacylglycerols is mediated by hormone-sensitive lipase (HSL) under stimulation of catecholamines (Nilsson , 1989;Sumner and McNamara, 2007;Elkins and Spurlock, 2009). Yet, the exact physiological role of HSL in maintenance of energy homeostasis in dairy cows is not fully understood.…”
Section: Introductionmentioning
confidence: 99%